SUBGRADIENT MINIMIZATION METHOD WITH DESCENT VECTORS CORRECTION BY MEANS OF TRAINING RELATIONS PAIRS - V. N. Krutikov; Ya. N. Vershinin (Вестник Кемеровского государственного университета, 2014)
The paper introduces a conjugate subgradient method whose descent is corrected by a pair of current training relations. The convergence of the method is proved on strictly convex functions. According to the numerical experiment, the method is effective at non-smooth high-dimensional minimization problems. By memory cost, theproposed method is similar to the conjugate gradient method, and at smooth high-dimensional singular functions its convergence rate is not inferior to tha of the conjugate gradient method.